Modified extragradient algorithms for solving equilibrium problems. (2nd November 2018) - Hieu, Dang Van; Cho, Yeol Je; Xiao, Yi-bin
ABSTRACT: In this paper, we introduce some new algorithms for solving the equilibrium problem in a Hilbert space which are constructed around the proximal-like mapping and inertial effect. Also, some convergence theorems of the algorithms are established under mild conditions. Finally, several experiments are performed to show the computational efficiency and the advantage of the proposed algorithm over other well-known algorithms.